Mesenchymal Stem Cell Immunomodulation: A Novel Intervention Mechanism in Cardiovascular Disease - Wang, Yueyao; Qi, Zhongwen; Yan, Zhipeng; Ji, Nan; Yang, Xiaoya; Gao, Dongjie; Hu, Leilei; Lv, Hao; Zhang, Junping; Li, Meng (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem cells (MSCs) are the member of multipotency stem cells, which possess the capacity for self-renewal and multi-directional differentiation, and have several characteristics, including multi-lineage differentiation potential and immune regulation, which make them a promising source for cell therapy in inflammation, immune diseases, and organ transplantation. In recent years, MSCs have been described as a novel therapeutic strategy for the treatment of cardiovascular diseases because they are potent modulators of immune system with the ability to modulating immune cell subsets, coordinating local and systemic innate and adaptive immune responses, thereby enabling the formation of a stable inflammatory microenvironment in damaged cardiac tissues. In this review, the immunoregulatory characteristics and potential mechanisms of MSCs are sorted out, the effect of these MSCs on immune cells is emphasized, and finally the application of this mechanism in the treatment of cardiovascular diseases is described to provide help for clinical application.